Investigation of heavy metal accumulation in soil, water and plants in areas with intensive horticulture - Silva, Laércio Santos [UNESP]; Galindo, Izabel Cristina de Luna; Gomes, Romário Pimenta [UNESP]; Filla, Vinícius Augusto [UNESP]; Campos, Milton César Costa; de Freitas, Ludmila; de Oliveira, Ivanildo Amorim; Marques, Karina Patrícia Prazeres; de Souza, Edicarlos Damacena; Cazzeta, Jairo Osvaldo [UNESP] (Southern Cross Publishing, 2019)
The content and availability of heavy metals in intensively cultivated soils are important issues because these metals are potential environmental contaminants and toxic to living beings. Thus, the aim of this study was to evaluate the levels of Cd, Mn, Cu, Pb, Ni and Zn available in the soil of five agricultural areas compared to the soil of adjacent native forests, to determine the risk of soil, water and plant contamination. A total of 180 soil samples were collected at two depths (0.00 - 0.10 and 0.10 - 0.30 m), and edible samples were extracted from plants cultivated in these soils. Water samples were taken from reservoirs commonly used to irrigate these crops and from well water used for human consumption. All the samples were subjected to heavy metal extraction methods (HNO 3 + HCl + DTPA) and measurements were carried out by atomic absorption spectrometry. The results showed that soil with intensive agricultural inputs increased Mn, Cu and Zn levels. High levels of Ni were found even in agricultural and forest soils, indicating that this may be associated with its presence in the original soil material. Pb and Ni levels exceeded the maximum values allowed by ANVISA (Brazilian Health Regulatory Agency) for all plant samples examined. Bell pepper and chard showed the highest levels of Pb and Ni, suggesting that these species accumulate more Pb and Ni compared to other species studied. Levels of Cd, Ni and Pb surpassed the values established by CONAMA (National Council for the Environment) for human consumption and irrigation water, and the levels were influenced by seasonal rainfall. Preventive monitoring and planning of fertilizer applications, in order to avoid fertilizing the soil near the rainy season, are alternatives to establish normal heavy metal levels in human consumption and irrigation water. Moreover, bell pepper and chard should not be grown in Pb and Ni contaminated soils.
Keywords: Agricultural management; Agriculture; Anthropic action; Bioavailability; Environmental pollution; Potentially toxic element